(untitled) (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: HBeAg status in chronic hepatitis B patients is important for outcome and treatment Objective: The purpose of the present study was to see the status of HBeAg Chronic Hepatitis B (CHB) patients. Methodology: This cross sectional study was conducted in the Department of Virology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka between July 2010 to June 2011. Serologically diagnosed CHB patients were enrolled for the study. The HBV DNA was quantified. Samples were tested for HBeAg with ELISA kit. Results: A total of 200 serologically diagnosed CHB patients were enrolled for the study. Among the total study population, HBeAg positive CHB patients were 74(37%) cases and HBeAg negative patients were 126 (63%) cases. Among the HBeAg negative patients, viral load was less and patients were significantly older. The mean viral load of HBeAg positive and HBeAg negative was 64012042 and 2.83i2.55 respectively. HBV DNA was a more reliable indicator of the presence of virus than HBeAg, and was detected in 98.65% (73/74) HBeAg positive carriers, and in 66.67% (84/126) HBeAg negative patients. Conclusion: HBeAg negativity is more prevalent among the CHB patients in Bangladesh. J Shaheed Suhrawardy Med Coll, 2014; 6(2):60-63